Effects of Cytochrome P450 Inhibitors on Itraconazole and Fluconazole Induced Cytotoxicity in Hepatocytes - Nhareet Somchit; Chong Sock Ngee; Azhar Yaakob; Zuraini Ahmad; Zainul Amiruddin Zakaria (Journal of Toxicology)
Itraconazole and fluconazole have been reported to induce hepatotoxicity in patients. The present study was designed to investigate the role of cytochrome P450 inhibitors, SKF 525A, and curcumin pretreatment on the cytotoxicity of antifungal drugs fluconazole and itraconazole. For 3 consecutive days, female rats were administered daily SKF 525A or curcumin (5 and 25 mg/kg). Control rats received an equivalent amount of dosed vehicle. The animals were anaesthetized 24 hours after receiving the last dose for liver perfusion. Hepatocytes were then exposed to various concentrations of antifungal drugs. In vitro incubation of hepatocytes with itraconazole revealed significantly lower viability when compared to fluconazole as assessed by lactate dehydrogenase, aspartate aminotransferase and alanine aminotransferase activities. The cytotoxicity of itraconazole was enhanced when incubated with hepatocytes pretreated with SKF 525A. SKF 525A had no effects on the cytotoxicity of fluconazole. Curcumin failed to either increase or decrease the cytotoxicity of both antifungal drugs. ATP levels also showed significant decrease in both itraconazole and fluconazole incubated hepatocytes. However, SKF 525A pretreated hepatocytes had significantly lower ATP levels after itraconazole incubations. Collectively, these results confirm the involvement of cytochrome P450 in the cytoprotection in itraconazole induced hepatocyte toxicity. Differences of the effects of SKF 525A on the cytotoxicity induced by itraconazole and fluconazole may be due to the differences on the metabolism of each antifungal drug in vivo.